Embeddedness and sequentiality in social media - Reeves, Stuart; Brown, Barry (2016)
Over the last decade, there has been an explosion of work around social media within CSCW. A range of perspectives have been applied to the use of social media, which we characterise as aggregate, actor-focussed or a combination. We outline the opportunities for a perspective informed by ethnomethodology and conversation analysis (EMCA)—an orientation that has been influential within CSCW, yet has only rarely been applied to social media use. EMCA approaches can complement existing perspectives through articulating how social media is embedded in the everyday lives of its users and how sequentiality of social media use organises this embeddedness. We draw on a corpus of screen and ambient audio recordings of mobile device use to show how EMCA research is generative for understanding social media through concepts such as adjacency pairs, sequential context, turn allocation / speaker selection, and repair.